Evaluating in vivo efficacy – toxicity profile of TEG001 in humanized mice xenografts against primary human AML disease and healthy hematopoietic cells. Issue 1 (12th March 2019) - Johanna, Inez; Straetemans, Trudy; Heijhuurs, Sabine; Aarts-Riemens, Tineke; Norell, Håkan; Bongiovanni, Laura; de Bruin, Alain; Sebestyen, Zsolt; Kuball, Jürgen
Abstract : Background: γ9δ2T cells, which express Vγ9 and Vδ2 chains of the T cell receptor (TCR), mediate cancer immune surveillance by sensing early metabolic changes in malignant leukemic blast and not their healthy hematopoietic stem counterparts via the γ9δ2TCR targeting joined conformational and spatial changes of CD277 at the cell membrane (CD277J). This concept led to the development of next generation CAR-T cells, so-called TEGs: αβT cells Engineered to express a defined γδTCR. The high affinity γ9δ2TCR clone 5 has recently been selected within the TEG format as a clinical candidate (TEG001). However, exploring safety and efficacy against a target, which reflects an early metabolic change in tumor cells, remains challenging given the lack of appropriate tools. Therefore, we tested whether TEG001 is able to eliminate established leukemia in a primary disease model, without harming other parts of the healthy hematopoiesis in vivo. Methods: Separate sets of NSG mice were respectively injected with primary human acute myeloid leukemia (AML) blasts and cord blood-derived human progenitor cells from healthy donors. These mice were then treated with TEG001 and mock cells. Tumor burden and human cells engraftment were measured in peripheral blood and followed up over time by quantifying for absolute cell number by flow cytometry. Statistical analysis was performed using non-parametric 2-tailed Mann-Whitney t-test. Results: We successfully engrafted primary AML blasts and healthy hematopoietic cells after 6–8 weeks. Here we report that metabolic cancer targeting through TEG001 eradicated established primary leukemic blasts in vivo, while healthy hematopoietic compartments derived from human cord-blood remained unharmed in spite of TEGs persistence up to 50 days after infusion. No additional signs of off-target toxicity were observed in any other tissues. Conclusion: Within the limitations of humanized PD-X models, targeting CD277J by TEG001 is safe and efficient. Therefore, we have initiated clinical testing of TEG001 in a phase I first-in-human clinical trial (NTR6541; date of registration 25 July 2017).